Polypropylene fiber for fiber reinforced cement composite material
By using polypropylene fiber reinforced cement composite materials, the problem of insufficient mechanical performance in the prior art composite materials in construction applications is solved, and high toughness, tensile strength and good mechanical properties are improved.
Patent Information
- Application Number
- CN202380055417.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-19
- Filing Date
- 2023-06-09
- Publication Date
- 2025-03-28
AI Technical Summary
When used in the construction industry, existing composite materials are difficult to meet the needs of high toughness, tensile strength and cracking deformation characteristics, especially under complex mechanical properties and environmental conditions.
Polypropylene fibers are used, which consist of a polypropylene matrix, a surf modifier and a surfactant or lubricant, and are produced by an extrusion and melt spinning process for reinforcement of cement composites.
The mechanical properties of cement composites are significantly improved, including fracture modulus, elastic modulus and low specific energy, and are suitable for building components that require good mechanical properties, such as roof tiles.
Smart Images

Figure CN119731379A_ABST
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims priority to U.S. Provisional Application No. 63 / 351,109, filed on June 10, 2022, and U.S. Provisional Application No. 63 / 371,193, filed on August 19, 2022, the entire contents of which are incorporated herein by reference. Background Art
[0003] In recent years, there has been considerable growth in the use of composite materials in the construction industry, such as concrete and mortar reinforced with fibers. Fiber cement products are used worldwide for their versatility as corrugated and flat roofing materials, cladding panels, and water containers found in a wide range of construction and agricultural applications. The main reason for adding fibers to the cement matrix is to improve the toughness, tensile strength, and crack deformation characteristics of the resulting composite material. Summary of the invention
[0004] This Summary is provided to introduce a series of concepts that are further described in the Detailed Description below. This Summary is not intended to identify key or essential features of the claimed subject matter, nor is it intended to be used as an aid in limiting the scope of the claimed subject matter.
[0005] In one aspect, embodiments disclosed herein relate to a polypropylene fiber, comprising: a polypropylene matrix; at least one surface modifier; and at least one additive selected from a surfactant, a lubricant, or a mixture thereof.
[0006] On the other hand, embodiments disclosed herein relate to a method for producing polypropylene fibers, comprising the steps of: (i) mixing polypropylene with a surface modifier during extrusion, and (ii) melt spinning the composition obtained from step (i) to produce the polypropylene fibers, wherein a surfactant is added to step (i) and / or a lubricant is applied to the fibers during step (ii).
[0007] On the other hand, embodiments disclosed herein relate to a reinforced cement composite material comprising: a cementitious matrix; polypropylene fibers comprising a polypropylene matrix, at least one surface modifier and at least one additive selected from a surfactant, a lubricant or a mixture thereof; a cellulose component; and optionally, a limestone component.
[0008] On the other hand, embodiments disclosed herein relate to an article comprising a reinforced cement composite material, the reinforced cement composite material comprising: a cementitious matrix; polypropylene fibers comprising a polypropylene matrix, at least one surface modifier and at least one additive selected from a surfactant, a lubricant or a mixture thereof; a cellulose component; and optionally, a limestone component.
[0009] On the other hand, embodiments disclosed herein relate to a roof tile comprising a reinforced cement composite material, the reinforced cement composite material comprising: a cementitious matrix; polypropylene fibers comprising a polypropylene matrix, at least one surface modifier and at least one additive selected from a surfactant, a lubricant or a mixture thereof; a cellulose component; and optionally, a limestone component.
[0010] Other aspects and advantages of the claimed subject matter will become apparent from the following description and appended claims. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] Figure 1A The modulus of rupture (MOR) of cementitious composites produced by the suction and pressing process at 10 days (10d) of cure and after accelerated aging (100C) are shown.
[0012] Figure 1B Shown are the modulus of rupture (MOR) of cementitious composites produced by the Hatschek process at 10 days (10d) of cure and after accelerated aging (100C).
[0013] Figure 1C The limit of proportionality (LOP) of cementitious composites produced by the suction-pressure process at 10 days (10 d) of cure and after accelerated aging (100 C) are shown.
[0014] Figure 1D The limit of proportionality (LOP) of cementitious composites produced by the Hatschek process at 10 days (10d) of cure and after accelerated aging (100C) are shown.
[0015] Figure 1E The modulus of elasticity (MOE) of cementitious composites produced by the suction-pressure process at 10 days (10 d) of curing and after accelerated aging (100 C) are shown.
[0016] Figure 1F Shown are the modulus of elasticity (MOE) of cementitious composites produced by the Hatschek process at 10 days (10d) of cure and after accelerated aging (100C).
[0017] Figure 1G The specific energy (SE) of cementitious composites produced by the suction-pressure process at 10 days (10 d) of cure and after accelerated aging (100 C) are shown.
[0018] Figure 1H The specific energy (SE) of cementitious composites produced by the Hatschek process at 10 days (10d) of cure and after accelerated aging (100C) is shown.
[0019] Figure 2A Shown is an image scanning electron microscopy (SEM-BSE) of the polished surface of the composite reinforced with K1 fibers.
[0020] Figure 2B Shown is an image scanning electron microscopy (SEM-BSE) of the polished surface of the composite reinforced with PP COMM fibers.
[0021] Figure 3A Shown are SEM micrographs of the composite material reinforced with K1 fibers after accelerated aging (100C) at 100 cycles.
[0022] Figure 3B Shown are SEM micrographs of composites reinforced with PVA fibers after accelerated aging (100C) at 100 cycles.
[0023] Figure 4A The water absorption (WA) of cementitious composites produced by the suction-pressure process at 10 days (10 d) of curing and after accelerated aging (100 C) is shown.
[0024] Figure 4B Shown is the water absorption (WA) of cementitious composites produced by the Hatschek process at 10 days (10d) of cure and after accelerated aging (100C).
[0025] Figure 4C The bulk density (BD) of cementitious composites produced by the suction-pressure process at 10 days (10 d) of curing and after accelerated aging (100 C) is shown.
[0026] Figure 4D The bulk density (BD) of cementitious composites produced by the Hatschek process at 10 days (10 d) of cure and after accelerated aging (100 C) is shown.
[0027] Figure 4E The apparent porosity (AP) of cementitious composites produced by the suction-pressure process at 10 days (10 d) of curing and after accelerated aging (100 C) is shown.
[0028] Figure 4FThe apparent porosity (AP) of cementitious composites produced by the Hatschek process at 10 days (10d) of cure and after accelerated aging (100C) is shown. DETAILED DESCRIPTION
[0029] The present disclosure relates to polypropylene fibers and fiber reinforced cementitious composites containing the polypropylene fibers. The reinforced cementitious composites of the present disclosure are particularly suitable for applications requiring good mechanical properties, including building elements such as roof tiles. The polypropylene fibers in the present disclosure exhibit improved performance as a reinforcing element to ensure ductile properties of cementitious products.
[0030] In one aspect, embodiments disclosed herein relate to polypropylene fibers comprising: a polypropylene matrix; at least one surface modifier; and at least one additive selected from a surfactant, a lubricant, or a mixture thereof.
[0031] The term "polypropylene" as used in this specification refers to propylene homopolymers, propylene random copolymers, heterophasic propylene copolymers and mixtures thereof.
[0032] In one or more embodiments, the polypropylene comprises at least one comonomer selected from ethylene and C4 to C8 alpha-olefins, wherein the weight percent (wt%) of the comonomer ranges from a lower limit selected from 0.5 wt%, 1 wt%, or 5 wt% to an upper limit selected from 2.5 wt%, 5 wt%, or 10 wt%, based on the weight of the polypropylene, wherein any lower limit can be combined with any upper limit.
[0033] In one or more embodiments, the polypropylene is a heterophasic polypropylene including a rubber phase dispersed in a continuous phase of polypropylene, wherein the rubber phase includes propylene and at least one comonomer selected from ethylene, C4 to C8 alpha-olefins, wherein the comonomer is present in the rubber phase in a weight percentage (wt%) range selected from any one of 5wt%, 10wt%, 15wt% and 20wt% to any one of 50wt%, 60wt%, 70wt% and 75wt%, wherein any lower limit can be paired with any upper limit. The rubber phase can be based on the weight of the heterophasic polypropylene in a weight percentage (wt%) range selected from any one of 2wt%, 3wt%, 5wt% and 10wt% to any one of 50wt%, 60wt%, 70wt% and 75wt%, wherein any lower limit can be paired with any upper limit. In a specific embodiment, the polypropylene is a homopolymer.
[0034] In one or more embodiments, the melt flow index (230°C / 2.16 kg) of the polypropylene measured according to ASTM D1238 ranges from a lower limit selected from 10 g / 10 min, 14 g / 10 min, or 16 g / 10 min to an upper limit selected from 40 g / 10 min, 26 g / 10 min, or 20 g / 10 min, wherein any lower limit can be combined with any upper limit.
[0035] In one or more embodiments, the polypropylene is a homopolymer having a melt flow index (230°C / 2.16kg) ranging from 10 g / 10 min to 30 g / 10 min as measured according to ASTM D1238. An example of the polypropylene used is PP H216 provided by Braskem.
[0036] The term "surface modifier" as used in this specification refers to organic or inorganic fillers and mixtures thereof. The "surface modifier" can promote physical adhesion of the composite cement to the fiber surface. In one embodiment, the surface modifier is inorganic and is selected from the group consisting of talc, calcium carbonate, calcium hydroxide, mica, calcium silicate, clay, kaolin, alumina, silica, wollastonite, magnesium carbonate, magnesium hydroxide, zinc oxide, titanium oxide, barium sulfate, zinc sulfate, and combinations thereof.
[0037] In a specific embodiment, the surface modifier is calcium carbonate. The surface modifier particles are optionally coated, or they present a surface treatment to improve their hydrophobicity and / or compatibility with the polypropylene matrix. In a specific embodiment, the surface modifier is a coated calcium carbonate. In one embodiment, the surface modifier is used in the form of a masterbatch. An example of a coated calcium carbonate suitable for use in the present disclosure is prepared by Immerys TM Provided by FiberLink 201S.
[0038] In one embodiment, the surface modifier is present in a weight percentage range based on the weight of the polypropylene fiber with a lower limit selected from 0.3wt%, 0.5wt%, 0.7wt%, 1.0wt% and an upper limit selected from 20wt%, 15wt%, 10wt%, 5wt%, wherein any lower limit can be combined with any upper limit.
[0039] The surface modifier can be incorporated into the polypropylene matrix by extrusion.
[0040] In one or more embodiments, the surface modifier is FiberLink 201S calcium carbonate and is present in a weight percent (wt %) range of 0.5 wt % to 10.0 wt % based on the weight of the polypropylene fiber.
[0041] The term "surfactant" as used in this specification refers to ionic surfactants, nonionic surfactants and amphoteric surfactants or combinations thereof. In one embodiment, the surfactant may be selected from the following: sulfates, sulfonates, phosphates, carboxylates, amines, quaternary ammoniums, alcohols, acids, ethoxylates and combinations thereof. The surfactant may have a carbon chain containing 8 to 13 carbon atoms. In another embodiment, the surfactant is a fatty alcohol comprising ethylene oxide and / or propylene oxide, thereby allowing controlled adhesion to the cementitious matrix.
[0042] An example of a surfactant suitable for use in the present disclosure is Alkomol L306 (manufactured by Oxiteno TM Provided), ethoxylated fatty acid esters and ethoxylated alcohol phosphates. When present, the amount of surfactant in the fiber ranges from a lower limit selected from 0.3wt%, 0.4wt% or 0.5wt% to an upper limit selected from 7wt%, 5wt% or 3wt%, based on the weight of the polypropylene fiber, wherein any lower limit can be combined with any upper limit. The surfactant can be added to the polypropylene matrix by extrusion. In one or more embodiments, the amount of surfactant in the fiber ranges from a lower limit selected from 0.5wt% to 5.0wt%.
[0043] Lubricants, also known as "finish oils," "spin finishes," or "finishes," can be used during the production of polypropylene fibers. During processing and subsequent handling, polyolefin resins tend to develop high static charges and excessive tension as they pass through guides, godet rollers, and other machine parts. Therefore, lubricants containing various compounds can be applied to the surface of polypropylene fibers during the spinning and stretching production stages. An example of a lubricant suitable for use in the present disclosure is Marlube NC-90. When the fibers are produced, the lubricant can be applied to the fibers during the spinning process.
[0044] In one or more embodiments, the polypropylene fibers exhibit a rheological polydispersity index determined according to ASTM D4440 (Plate Rheology Test) ranging from a lower limit of 1.75, 2, or 2.25 to an upper limit of 4, 3.5, or 3, wherein any lower limit can be combined with any upper limit.
[0045] In one or more embodiments, the polypropylene fibers exhibit a Mw / Mn, as determined by GPC, ranging from a lower limit of 2, 2.5, or 3 to an upper limit of 5.5, 5, or 4.90, wherein any lower limit can be combined with any upper limit.
[0046] In one or more embodiments, the polypropylene fiber exhibits a tenacity measured according to NBR13385 DE 05 / 1995 ranging from a lower limit of 7 cN / dtex, 8 cN / dtex, or 9 cN / dtex to an upper limit of 15 cN / dtex, 14 cN / dtex, 13 cN / dtex, 12 cN / dtex, 11 cN / dtex, 10.5 cN / dtex, or 10 cN / dtex, wherein any lower limit can be combined with any upper limit.
[0047] In one or more embodiments, the polypropylene fiber exhibits an elongation measured according to NBR 13385 DE 05 / 1995 ranging from a lower limit of 5%, 6%, or 7% to an upper limit of 18%, 16%, 14%, or 12%, wherein any lower limit can be combined with any upper limit.
[0048] Polypropylene fibers can be prepared using conventional extrusion methods to produce high tenacity monofilaments.
[0049] On the other hand, embodiments disclosed herein relate to a method for producing polypropylene fibers, the method comprising the steps of: (i) mixing polypropylene with at least one surface modifier during extrusion, (ii) melt spinning the composition obtained in step (i) to produce fibers, wherein a surfactant is added to step (i) and / or a lubricant is applied to the fibers during step (ii).
[0050] In one embodiment, fiber is prepared by the melt spinning process using a spinning assembly. The spinning assembly includes a three-piece filter, a distributor (which distributes molten polymer onto the die surface) and a die. In this way, spinning holes and cooling rates are used in the production process of the spinning melt head to obtain filaments with high tenacity in a narrow performance dispersion range. The spinning process may include two steps: spinning / bobbin and stretching. Afterwards, the fiber can be cut into small filaments, wherein the size will depend on the final application requirements. In one embodiment, the fiber is cut into filaments with a length of 5mm to 20mm.
[0051] On the other hand, embodiments disclosed in this specification relate to a feasible cementitious material using cellulose pulp and polypropylene as reinforcing components. In this regard, embodiments disclosed in this specification relate to a fiber-reinforced cement composite material formed by a cement matrix and polypropylene fibers according to one or more embodiments, wherein the fiber-reinforced cement composite material comprises: a cement matrix; polypropylene fibers, the polypropylene fibers comprising a polypropylene matrix, at least one surface modifier and at least one additive selected from a surfactant, a lubricant and a mixture thereof; a cellulose component; and optionally, a limestone component.
[0052] The term "cement" as used in this specification refers to any conventional cement formulation, including Portland cement. In addition, the cement formulation may include sand, siliceous loam, pozzolan, diatomaceous earth (DE), pyrite, alumina, limestone, clay, carbon dioxide, calcium oxide, gypsum and other suitable fillers and additives.
[0053] According to one embodiment, CP V-ARI type ordinary Portland cement (OPC) corresponding to ASTM C150 (Type III) is used in the fiber reinforced cement composite material disclosed in this specification because it has a finer particle size and higher reactivity. This type of cement contains a higher level of tricalcium silicate (C3S) and dicalcium silicate (C2S) for forming CSH.
[0054] As used herein, the term "cellulose component" refers to any cellulose component. Examples include unbleached, unrefined eucalyptus (Eucalyptus grandis) kraft pulp obtained from Suzano S / A of Brazil. The physical properties of the unbleached eucalyptus pulp are: length 0.83 mm, width 16.4 mm, fiber material 18.17 g, fine fiber content 25.7% by mass.
[0055] In one embodiment, the cement matrix is present in the fiber reinforced cement composite in a weight percent (wt %) range of 40% wt to 80% wt.
[0056] In one embodiment, the polypropylene fiber is present in the fiber reinforced cement composite in a weight percentage range of a lower limit selected from 0.3wt%, 0.5wt%, 0.7wt% or 1.0wt% and an upper limit selected from 5wt%, 4wt%, 3wt% or 2.5wt%, based on the total weight of the fiber reinforced cement composite, wherein any lower limit can be paired with any upper limit.
[0057] Fiber length is an important feature to achieve the performance of the reinforced cement composite material of the present invention. In this regard, the fiber length range used is 7mm to 14mm. In one or more embodiments, the fiber length ranges from 8mm to 12mm.
[0058] In one embodiment, the cellulose component is present in the fiber reinforced cement composite in a weight percentage range of a lower limit selected from 0.3wt%, 0.5wt%, 0.7wt% or 1.0wt% and an upper limit selected from 10wt%, 5wt%, 3wt% or 2.5wt%, based on the total weight of the fiber reinforced cement composite, wherein any lower limit can be paired with any upper limit.
[0059] In one embodiment, the limestone is present in the fiber reinforced cement composite in a weight percent (wt %) range of 15% wt to 40% wt.
[0060] The fiber reinforced cement composites of the present disclosure exhibit improved mechanical properties (modulus of rupture, modulus of elasticity) and low specific energy when compared to conventional cement reinforced with polypropylene fibers.
[0061] The fiber reinforced cement composites of the present disclosure may be used in a variety of applications, such as roof tiles, flat panels or corrugated panels (eg, wall panels) for cladding or building elements.
[0062] Fiber reinforced cementitious composites can be prepared by any method known in the art, including industrial and laboratory methods. Examples of such methods for preparing reinforced cementitious composites are described below and in more detail in the literature.
[0063] Industrial Technology (Hatschek)
[0064] The Hatschek process is the most widely used process for producing fiber cement components. The Hatschek process involves the production of fiber cement sheets by stacking thin layers made of a suspension (slurry) of cement, fibers, mineral admixtures and water, and its process is similar to papermaking. The first step is to prepare the slurry, which involves mixing the appropriate proportion of solid materials with water at a low solid concentration (10%-15% of the total mass). Cement, asbestos, cellulose fibers, limestone filler and water are the most commonly used materials in asbestos cement technology. The slurry is then conveyed to a barrel with a screen cylinder, where the wet solid material is deposited. Next, a running felt removes the material from the screen cylinder, thereby forming a green lamina. Before the thin layer is transferred to a forming cylinder for stacking, a vacuum is applied to remove water from the thin layer. Finally, the green sheet is cut, formed (corrugated sheets and accessories), and cured.
[0065] Suction and pressure process
[0066] The suction-pressure process is a laboratory-scale method that simulates the industrial method for fiber cement production, the Hatschek process. Composites reinforced with cellulose pulp were prepared using the suction-pressure process. In this study, the formulation was based on commercial raw materials used in the fiber cement industry.
[0067] Examples
[0068] Polypropylene fibers were produced by mixing polypropylene with 80% of FiberLink 201S calcium carbonate to obtain a masterbatch compound. Polypropylene was extruded with 1.0% to 4% of the masterbatch compound and 1.25% of Alkomol 306L. (ii) The composition obtained in step (i) was melt spun to produce fibers, wherein a surfactant was added in step (i) and / or a lubricant was applied to the fibers during step (ii).
[0069] A specific example of the method for producing the polypropylene fiber will be described below, but is not limited thereto.
[0070] Step 1 (extrusion): The fibers were extruded on a PTI 4" / 30d extruder from the manufacturer Neumag at a temperature of about 260°C, a melt pressure of 90 bar and a rotation speed of 45 rpm. The die had 6500 holes with a diameter of 0.35 mm and a length of 1.75 mm. The filaments obtained by spinning at a speed of 500 m / min using 10% Pulcra Stantex 7292 spin finish had a titer of about 5.5 dtex.
[0071] Step 2 (melt spinning): The die used had 6500 holes with a diameter of 0.35 mm and a length of 1.75 mm. The filaments obtained by spinning at a speed of 500 m / min using 10% Pulcra Stantex 7292 spin finish had a fineness of about 5.5 dtex.
[0072] Step 3 (drawing): The filaments were drawn on five stages of heated rollers at a speed of about 80 m / min. The final fineness was 1.1 dtex.
[0073] Step 4 (Chopping): After applying a 10% Pulcra spin finish bath, the filaments were chopped at a length of about 9.8 mm at a cutting speed of 80 m / min.
[0074] Three types of polypropylene (PP) fibers (K1, K2 and B6) were used in the tests. Fibers K1 and K2 are according to the invention, while fiber B6 is used for comparison. The formulations and some mechanical and physical properties of the fibers are listed in Tables 1 and 2, respectively.
[0075] Table 1 - Formulations of fibers tested (comparative and inventive fibers).
[0076]
[0077] *Based on ASTM D1238
[0078] Table 2 - Mechanical and physical properties of polypropylene fibers (comparative and inventive fibers).
[0079]
[0080] K1, K2 and B6 were used to prepare fiber reinforced cement composites by the Hatschek method and the "suction-pressure process" discussed previously. The flat pads were cured by industrial methods and evaluated after 10 days (10d) and after 100 cycles (100C). Ordinary Portland cement (OPC) of type CP V-ARI (corresponding to ASTM C 150, type III) was selected because of its finer particle size and higher reactivity. In addition, limestone was used in the formulation. This type of cement contains higher levels of tricalcium silicate (C3S) and dicalcium silicate (C2S) for the formation of CSH.
[0081] The cement and limestone particle size distribution was evaluated by a laser particle size analyzer (Malvern Mastersizer S long bed, version 2.19). 50% of the cement and limestone particles by mass were smaller than 10.09 μm and 12.96 μm, respectively. The particle size distribution of both raw materials was similar.
[0082] Quantitative chemical analysis was performed using a PANalytical Axios Advanced X-ray fluorescence device. The main oxide compositions of cement and limestone are: SiO2: 14.70, 9.40; CaO: 67.20, 39.10; Al2O3: 4.07, 2.16; Fe2O3: 3.50, 1.25; MgO: 3.13, 8.90. The specific surface area (determined using the BET method) and specific density of the raw materials were measured. Similar specific surface area values may be important to avoid water competition between the raw materials in the system. The specific density of OPC is 3.10 g / cm 3 , with a specific surface area of 1.10m 2 / g, the specific density of limestone is 2.80g / cm 3 , with a specific surface area of 1.14m 2 / g.
[0083] A specific example of the composition of the fiber reinforced cement composite material is:
[0084] - 3.5 wt% cellulose kraft pulp (unbleached, unrefined eucalyptus (Eucalyptus grandis) kraft pulp). Kraft pulp was provided by Suzano S / A, Brazil;
[0085] - 65 wt% of ordinary Portland cement (OPC) of CP V-ARI type;
[0086] - 30 wt% limestone; and
[0087] - 1.5 wt% of fibres according to the invention (and comparative forms, as described below).
[0088] For the purpose of the tests, in addition to the fibers K1, K2 and B6, polypropylene (PP) from Saint-Gobain Industry (PP COM) and polyvinyl alcohol (PVA) fibers from Kuraray SA used in the cement industry were used as comparisons. Both PP COM and PVA are commercially available.
[0089] Different types of fiber reinforced cement composites were prepared using K1, K2, B6, PP COM and PVA fibers, respectively. The mechanical properties of each fiber were tested as discussed below.
[0090] The suction-pressure process in the laboratory was carried out according to the following procedure: First, commercial bleached eucalyptus hardwood kraft pulp was dispersed in water at a speed of 3000rpm for 5min. Ordinary Portland cement CP V-ARI and limestone were added and stirred at a speed of 1000rpm for 5min. The mixture was transferred to a casting box and negative pressure (80kPa) was applied to remove excess water in the process. After this step, the fiber-cement composite was pressed at 3.2MPa for 5 minutes. The fiber-cement composite was cured in a sealed plastic bag at 29±2℃ for 2 days. Then, the board was placed in a hot bath at 60℃ for 5 days. The board was then placed on a workbench for 2 days and then immersed in water for 24 hours. The whole process totaled 10 days before testing.
[0091] Mechanical properties of composite materials
[0092] Mechanical testing was performed in a machine EMIC (model DL 30000) equipped with a 1 kN load cell. A four-point bending configuration was used to determine the modulus of rupture (MOR), limit of proportionality (LOP), modulus of elasticity (MOE), and specific energy (SE) values. The bending test used a span of 75 mm and a deflection rate of 5 mm / min. Equations 1, 2, and 3 define the MOR, LOP, and MOE, respectively:
[0093]
[0094] Where P is the maximum load, PLOP is the load at the point on the linear part of the load-deformation curve, Lv is the main span between supports, b and h are the specimen width and depth, respectively, and δ is the vertical displacement of the specimen.
[0095]
[0096] The specific energy shown in Equation 4 is defined as the energy absorbed during the bending test divided by the specimen cross-sectional area. The absorbed energy is obtained by integrating the area under the load deflection curve to the point corresponding to the load carrying capacity being reduced to 90% of the maximum value achieved.
[0097] Physical properties testing
[0098] The water absorption (WA), apparent porosity (AP) and bulk density (DA) values were obtained from the average of ten test specimens designed for each mixture according to the procedure prescribed in ASTM C 948-81 standard.
[0099] Soak / dry accelerated aging cycles
[0100] The immersion / drying accelerated aging test consists of a comparative analysis of the physical and mechanical properties of the composite material before and after the immersion / drying cycle. The specimens are continuously immersed in water at 20±5°C for 170 min, followed by an interval of 10 min, and then exposed to a temperature of 70±5°C in a ventilated oven for 170 min, followed by an interval of 10 min. The procedure is based on the recommendations of the EN 494 standard. Each immersion / drying combination represents a cycle, 100 cycles are performed and obtained from the average value of ten specimens for each mix design.
[0101] Scanning electron microscopy
[0102] A scanning electron microscope (SEM) and a secondary electron (SE) detector operated at 10.0 kV accelerating voltage were used to observe the surface fiber morphology. Energy dispersive X-ray spectroscopy (EDS) analysis was also performed. EDS evaluates the interaction of chemical elements used for fiber surface treatment (Santos et al., 2015). These tests were performed on the same surface specimens to obtain semi-quantitative compositional information. The samples were carbon coated before analysis in a Zeiss LEO 440 microscope.
[0103] Statistical analysis
[0104] Mechanical and physical tests were performed using a completely randomized test design with four treatments (PP COM, K1, K2, B6 and PVA) and ten replications. The effects of MOR, LOP, MOE, SE, WA, DA and PA were compared by Student's t-test with a 5% significance level. The ACTION statistical program was used.
[0105] Figures 1 and 2 and Tables 3 and 4 show the mechanical properties (modulus of rupture (MOR), limit of proportionality (LOP), modulus of elasticity (MOE) and specific energy (SE)) of cement-based composites prepared by the suction-pressure process and the Hatschek process at 10 days (10d) and after accelerated aging (100C), respectively. Tables 5 and 6 list the corresponding mean values, standard deviations and statistical analysis of the mechanical properties and physical properties, respectively.
[0106] The modulus of rupture (MOR) indicates the tensile strength when bent, as well as the fiber-matrix interaction and strain distribution. According to statistical analysis, reinforced cement-based composites with K1, K2 and PVA fibers produced by the suction-pressure process and Hatschek showed better results relative to other fibers when cured for 10d. These results may be related to the physical properties of the fibers (length and thickness), which improve the distribution of the fibers within the composite. Another factor contributing to these values is the new technology for processing and manufacturing PP fibers, which is being innovated to improve its performance. Note that the composite with the new generation of K1 fibers contributes 47% to the MOR value, and the composite with K2 fibers contributes 32% to the MOR value, relative to the PP COM fibers produced by the suction-pressure process and Hatschek process commonly used commercially in the cement industry. Figure 2 presents an SEM micrograph between K1 and PP COM fibers, which shows that the interaction between the fibers and cement is improved, which contributes to a better distribution of tension between the fibers and the matrix.
[0107] After 100 cycles of accelerated aging (100C), K1 composites produced by suction-pressure process as well as Hatschek process increased MOR values in cases involving 10d, which may be due to the synergistic effect between synthetic and plant fibers (cellulose pulp) and densification of cement matrix after the continuous process of cement hydration (which improves the fiber-matrix interface). Cellulose pulp is hydrophilic and absorbs water from the system through the continuous process of cement hydration. However, K1 fibers are hydrophobic and do not absorb water. Note that K1 fibers also show an increase in MOR relative to PVA fibers. In most cases, PVA fibers showed better results than PP fibers in the literature.
[0108] Table 3.1 - Mean values and standard deviations* of modulus of rupture (MOR), limit of proportionality (LOP), modulus of elasticity (MOE), specific energy (SE), water absorption (WA), bulk density (BD) and apparent porosity (AP) of composite cements reinforced with polypropylene fibers (PP COM, K1, K2, B6) and polyvinyl alcohol fibers (PVA) produced by the suction-pressure process at 10 days (10d) of curing and after 100 cycles of accelerated aging (100C).
[0109]
[0110] *Lower case letters and numbers (a, b, and c; 1, 2, and 3) in the same column indicate the comparison between the composite formulations at 10 d and 100 cycles, respectively.
[0111] Table 3.2
[0112]
[0113] *Lower case letters and numbers (a, b, and c; 1, 2, and 3) in the same column indicate the comparison between the composite formulations at 10 d and 100 cycles, respectively.
[0114] In Table 3.1 and Table 3.2, different letters and numbers indicate significant differences between the properties of the composites.
[0115] Figure 1C Results for Limit of Proportional (LOP) are shown, from which the properties and behavior of the fibers in the matrix can be inferred. The results show that at 10d, there is no significant difference between the two formulations. After 100C, the composites with PP COM and K1 show better results. This behavior of PP COM and K1 may indicate an improvement in the adhesion between the fibers and the matrix relative to the other formulations. The flat mat produced by the Hatschek process shows no difference in LOP and proportional modulus (MOE) both at 10 days and after 100C.
[0116] The MOE value indicates the stiffness of the specimen. The MOE values of cementitious composites reinforced with PP and PVA at 10d and 100C showed no significant difference between the two formulations. After 100C, the MOE value increased slightly, indicating that PP and PVA fibers can effectively increase the stiffness of the specimen (Zhang et al., 2022).
[0117] Table 4.1 - Mean values and standard deviations* of modulus of rupture (MOR), limit of proportionality (LOP), modulus of elasticity (MOE), specific energy (SE), water absorption (WA), bulk density (BD) and apparent porosity (AP) of flat mats reinforced with polypropylene fibers (PP COM, K1, K2, B6) and polyvinyl alcohol fibers (PVA) produced by the Hatschek process at 10 days (10d) of curing and after 100 accelerated aging cycles (100C).
[0118]
[0119]
[0120] *Lower case letters and numbers in the same column (a, b, and c; 1, 2, and 3) indicate comparisons between flat pad formulations at 10d and 100 cycles, respectively. Different letters and numbers indicate significant differences between composite properties.
[0121] Table 4.2
[0122]
[0123] *Lower case letters and numbers in the same column (a, b, and c; 1, 2, and 3) indicate comparisons between flat pad formulations at 10d and 100 cycles, respectively. Different letters and numbers indicate significant differences between composite properties.
[0124] At 10d and after 100C, the cementitious composites and flat mats reinforced with K1 showed higher specific energy (SE) results. The fact that the fibers presented similar surface areas suggests that the K1 fibers showed a better interaction with the cement matrix, increasing the sliding ability during bending and, therefore, the energy absorption, as observed through the specific energy values. However, after 100C, all fibers showed an increasing trend due to cement rehydration, but did not show the same behavior as the K1 fibers. The toughening of the cement matrix is related to several phenomena occurring during its fracture process, such as: matrix debonding, pull-out, bridging, and finally fiber fracture (snapping) (Almeida et al., 2013). Fiber pull-out is the main cause of the toughening mechanism and energy absorption of the composites. This strong bonding between the fibers and the matrix can be seen in the fracture surface images of the composites reinforced with K1 fibers ( Figure 3A ) shows that the SE results after 100C are different from those of PVA fibers ( Figure 3B ), the composites reinforced with K1 fibers showed good adhesion.
[0125] Overall, these physical results do not demonstrate significant differences in the water absorption (AA) and apparent density (PA) of the cementitious composites. However, the porosity of the composites reinforced with PP COM decreased slightly at 10 days and after 100C, on the other hand, these composites did not differ from the other formulations. The flat mats reinforced with PP COM had a higher water absorption at 10d and a higher porosity between the reinforcing fibers. This behavior can be related to the aspect ratio of the fibers (see Table 1), the distribution of the fibers in the matrix and the influence of the production process, which leads to difficulties in packing the composites and, therefore, to greater absorption and porosity. Another factor is the lower adhesion between the matrix fibers, which leads to a dominance of fiber pull-out and lower SE values. This characteristic can be a negative aspect, leading to the creation of defects in the microstructure of the composites.
[0126] Although only a few exemplary embodiments are described in detail above, it will be readily appreciated by those skilled in the art that many modifications may be made in the exemplary embodiments without substantially departing from the scope of the present invention. Therefore, all such modifications are intended to be included within the scope of the present disclosure as defined by the appended claims. In the claims, functional limitations are intended to cover structures described in this specification as performing the recited functions, which cover not only structural equivalents, but also equivalent structures.
Claims
1. A polypropylene fiber comprising: Polypropylene matrix, at least one surface modifier, At least one additive selected from surfactants, lubricants or mixtures thereof.
2. The polypropylene fiber according to claim 1, wherein The polypropylene matrix is a homopolymer.
3. The polypropylene fiber according to claim 1, wherein The polypropylene matrix comprises at least one comonomer selected from ethylene and C4 to C8 alpha-olefins, wherein the weight percentage (wt%) of the comonomer ranges from 0.5 wt% to 10 wt% based on the weight of the polypropylene.
4. The polypropylene fiber according to claim 1, wherein The polypropylene matrix is a heterophasic polypropylene comprising a rubber phase dispersed in a continuous polypropylene phase, wherein the rubber phase comprises propylene and at least one comonomer selected from ethylene, C4 to C8 α-olefins, wherein the comonomer is present in a weight percent (wt %) range of 5 wt % to 75 wt % of the rubber phase.
5. The polypropylene fiber according to claim 4, wherein The rubber phase is present in a weight percent (wt %) range of 2 wt % to 75 wt %, based on the heterophasic polypropylene.
6. A polypropylene fiber according to any one of the preceding claims, wherein The polypropylene matrix has a melt flow index (230° C. / 2.16 kg) in the range of 10 g / 10 min to 20 g / 10 min as determined according to ASTM D1238.
7. A polypropylene fiber according to any one of the preceding claims, wherein The surface modifier is selected from organic surface modifiers, inorganic surface modifiers and mixtures thereof.
8. A polypropylene fiber according to any one of the preceding claims, wherein The surface modifier is selected from the group consisting of talc, calcium carbonate, calcium hydroxide, mica, calcium silicate, clay, kaolin, alumina, silica, wollastonite, magnesium carbonate, magnesium hydroxide, zinc oxide, titanium oxide, barium sulfate, zinc sulfate, and combinations thereof.
9. A polypropylene fiber according to any one of the preceding claims, wherein The surface modifier is coated or has a surface treatment.
10. A polypropylene fiber according to any one of the preceding claims, wherein The surface modifier is coated calcium carbonate.
11. A polypropylene fiber according to any one of the preceding claims, wherein The surface modifier is present in a weight percent (wt %) range of 0.3 wt % to 20 wt % based on the weight of the polypropylene fiber.
12. A polypropylene fiber according to any one of the preceding claims, wherein The surfactant is selected from ionic surfactants, nonionic surfactants, amphoteric surfactants or a combination thereof.
13. A polypropylene fiber according to any one of the preceding claims, wherein The surfactant is selected from the group consisting of sulfates, sulfonates, phosphates, carboxylates, amines, quaternary ammonium, alcohols, acids, ethoxylates, and combinations thereof.
14. A polypropylene fiber according to any one of the preceding claims, wherein The surfactant is a fatty alcohol comprising ethylene oxide and / or propylene oxide.
15. A polypropylene fiber according to any one of the preceding claims, wherein The amount of surfactant in the fibers is 0.3 wt % to 7 wt % based on the weight of the polypropylene fibers.
16. A polypropylene fiber according to any one of the preceding claims, wherein The surface modifier and optionally the surfactant are incorporated into the polypropylene matrix by extrusion.
17. A polypropylene fiber according to any one of the preceding claims, wherein The lubricant is applied to the fibers during the spinning process.
18. A polypropylene fiber according to any one of the preceding claims, wherein The fibers have a rheological polydispersity index of 1.75 to 3.
19. A polypropylene fiber according to any one of the preceding claims, wherein The fiber has a Mw / Mn of 2 to 5.
5.
20. A polypropylene fiber according to any one of the preceding claims, wherein The tenacity of the fiber is 7 cN / dtex to 15 cN / dtex.
21. A polypropylene fiber according to any one of the preceding claims, wherein The elongation of the fibers is 5% to 18%.
22. A method for producing a polypropylene fiber according to any one of claims 1 to 21, comprising the steps of: (i) mixing polypropylene with a surface modifier during extrusion, and (ii) melt spinning the composition obtained in step (i) to produce said fibers, Therein, a surfactant is added to step (i) and / or a lubricant is applied to the fibers during step (ii).
23. The method according to claim 22, wherein: The fibers were further cut into filaments having a length of 5 mm to 20 mm.
24. A fiber reinforced cement composite material comprising: - cement matrix; as well as - Polypropylene fibers, the polypropylene fibers comprising: - Polypropylene matrix, - at least one surface modifier, - at least one additive selected from surfactants, lubricants and mixtures thereof; - a cellulose component; and - Optionally, a limestone component.
25. A composite material according to claim 24, comprising fibres according to any one of claims 1 to 21.
26. The composite material according to claim 24, wherein The length of the polypropylene fibers ranges from 7 mm to 14 mm.
27. The composite material according to claim 24, wherein The polypropylene fiber is present in a weight percent (wt %) range of 0.3 wt % to 5 wt % based on the total weight of the cement composite.
28. An article comprising the fiber reinforced cement composite material according to claim 24.
29. A roof tile comprising the fiber reinforced cement composite material according to claim 24.